An Islamic Perspective on Tofu Industry - Viki Viktoria Pitaloka Sari (Journal of Islamic Studies and Education, 2022)
Producing tofu in hamletKanoman uses the same process from soaking soybeans to molding tofu, the only ingredients used are soybean seeds and vinegar or water as a seasoning. The tools used in processing the average for production use selepan which is driven by a motor for the soybean milling process. The purpose of this study was to determine the principles of Islamic production for tofu making in Kanoman, Gagaksipat Village, Ngemplak District, Boyolali Regency. This research is a field research that focuses on tofu production. With data obtained from interviews and observations. The results of data analysis indicate that there is one production that does not meet production standards and the disposal of tofu production waste is dumped into the river becausethe producer does not consider the surrounding environment as a place that must be protected.